Effect of Ultrasonic Frequency on the Physical Absorption of CO2 - Baqdhimh Barashaid, Ali Abdullah (Universiti Teknologi PETRONAS, 2016)
In the oil and gas industry, the presence of carbon dioxide has been inconveineint to natural gas processing and transportation. Many technologies have been applied in order to tackle this problem. The most common technologies that have been used for CO2 capture from natural gas are absorption, adsorption, membranes and cryogenic distillation. Absorption has been found to be the most matured technology among others. However, for offshore oil and gas industries, a technology such as absorption will not be capable to take a place because of its excessive footprint (Conventional absorption column) which is not available in the offshore condition. Therefore, a compact contractor is required to reduce the size of the absorption process. Membrane contactor and the mechanical agitator are existed but each of them has its own limitations. Meanwhile, ultrasonic assisted absorption contactor (UAAC) is another alternative method for CO2 removal. Ultrasonic irradiation is a potential technology that has been applied in many processes and has showed a good impact on the result. For examples, it has been used as a method to disrupt and deflocculate waste activated sludge.